Bayesian Network approach in analyzing the sustainability of the cultural industry ‘the sacred’ Gringsing Weaving - Saskara, Ida Ayu Nyoman; Saraswaty, Amrita Nugraheni; Suryasih, Ida Ayu; Suasih, Ni Nyoman Reni; Dewani, I Dewa Ayu Made Natasah; Dew, Desak Made Marysha (Decision Science Letters, 2025)
Bali is a popular tourist destination in the world, and the main entry point for foreign tourists to Indonesia. Bali is also an area in Indonesia that is famous for producing woven fabrics, which have various characteristics in each region. Gringsing weaving is one of the traditional Balinese fabrics from Tenganan Village which is considered sacred and its manufacture takes quite a long time, and is carried out with special techniques that are very difficult. This study aims to analyze and map factors related to the sustainability of the Gringsing weaving cultural industry, using the Bayesian Network approach. The results of the FGD with related stakeholders mapped the structure that forms Gringsing industrial sustainability, such as income, social capital, incentives, natural capital, custom law, and traditional institutions. Further analysis was carried out using the Bayesian Network technique and GeNIe tools. In forming the structure of thinking about the sustainability of the Gringsing Weaving industry, the related factors include culture, traditional institutions, natural capital, social capital, to economic factors, such as income and special incentives from the government. Specifically, the role of traditional institutions and government (through special incentives) was analyzed, and it was found that both factors can increase the probability of the sustainability of the gringsing weaving industry. The results of the sensitivity analysis also show that the sustainability of the Gringsing weaving industry is highly influenced (sensitive) to the increasing role of traditional institutions.